+0  
 
0
57
2
avatar

What is -6t x 4m x (-m)?

Guest Aug 10, 2017
Sort: 

2+0 Answers

 #1
avatar+214 
0

I'm assuming you mean simplify? I'm gonna do that.

 

\(-6t*4m*(-m)\)

-m can be expressed as -1*m, and -6t can be expressed as -1*6t: \(-1*-1*6t*4m*m\)

-1 * -1 = 1: \(1*6t*4m*m=6t*4m*m\)

m * m = m2\(6t*4m*m=6t*4*(m*m)=6t*4*m^2\)

Factor out 2: \(2(3t*2m^2)\)

 

The simplest form of the expression is \((2(3t*2m^2))...or...(6t*4m^2)\)

Mathhemathh  Aug 10, 2017
 #2
avatar+6765 
0

It's not the simplest form ._.

\(-6t \cdot 4m \cdot (-m)\\ =(-6\cdot 4)\cdot(t\cdot m\cdot(-m))\\ =-24(-tm^2)\\ =24tm^2\)

Simplest form should be 24tm^2...

MaxWong  Aug 11, 2017

15 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details